Development and Evaluation of a New Technological Way of Engaging Patients and Enhancing Understanding of Drug Tolerability in Early Clinical Development: PROACT. Issue 6 (June 2016) - Hughes, Andrew; Landers, Donal; Arkenau, Hendrik-Tobias; Shah, Saj; Stephens, Richard; Mahal, Amrik; Simmons, Matthew; Lemech, Charlotte; Royle, Jennifer
Abstract Introduction During early clinical testing of a new medication, it is critical to understand and characterise patient tolerability. However, in early clinical studies, it is difficult for patients to contribute directly to the sponsors' understanding of a new compound. Patient reported opinions about clinical tolerability (PROACT) provides a new, simple and innovative way in which patients can collaborate using an application downloaded to a mobile computer or smartphone. Methods PROACT was designed with special consideration given to patient confidentiality, patient engagement and data security. A pilot study was conducted to investigate patient uptake of PROACT and to characterize clinical trial information it captured. Patients recruited to Phase I oncology trials at a UK center were eligible to participate but were required to have a tablet computer or smartphone. Patients used PROACT to upload audio/video messages that became available instantly to their clinical team, who were able to reply to the patient within PROACT. The patient's message was also analyzed, personally-identifiable information removed and anonymized information then made available to the sponsor in an analytics module for decision-making. In parallel, a patient focus group was engaged to provide feedback on communication needs during early clinical trials and the PROACT concept. Results Of the 16 patients informed of PROACT, 8 had a smart device and consented to take part. Use of PROACT varied and all messages volunteered were relevant and informative for drug development. Topics disclosed included tolerability impacts, study design, and drug formulation. Alignment with the clinical study data provided a richer understanding of tolerability and treatment consequences. This information was available to be shared among the clinical team and the sponsor, to improve patient support and experience. Patient forum feedback endorsed the concept and provided further information to enhance the application. Conclusion Overall, PROACT achieved proof of concept in this small pilot study and delivered a secure end-to-end system that protected patient privacy and provided preliminary insight into patient experiences beyond the usual clinical trial data set. The use of mobile devices to interact actively with participants in clinical trials may be a new way of engaging and empowering patients. Further validation of this technology in larger patient cohorts is ongoing. Funding AstraZeneca.